Pavement Damage Assessment on the Soekarno Hatta Km 1–5 Section in Balikpapan Through the PCI Method - Asmaningrum, Tri Hardiyanti; Zamzani, Muhamad Imron; Isabella, Mayati; Friber, Friber; Achmad, Radja Nikra (Fakultas Teknik Universitas Tanjungpura, 2025)
Pavement conditions along corridors with high volumes of heavy vehicle traffic tend to deteriorate more rapidly than their design service life would allow. Soekarno Hatta Road, Km 1–4 in Balikpapan City, is a strategic roadway that accommodates intensive freight traffic and exhibits significant pavement surface distress. This study aims to evaluate pavement surface condition along this segment using the Pavement Condition Index (PCI) method to determine damage levels and maintenance requirements. The data used consist of primary field survey data, including the identification of distress types, severity levels, and distress density for each 100-meter sample unit. The analysis results indicate that the dominant distresses are edge cracking (17.61%), depressions (15.91%), and surface corrugation (15.34%), suggesting the presence of both structural and functional pavement problems. PCI values vary along the roadway: the Km 1 and Km 3 segments are classified as Fair (average PCI of 63), whereas the Km 2 and Km 4 segments are classified as Poor (average PCI of 48 and 43, respectively). The findings demonstrate that heavy traffic loading, base-layer conditions, and pavement aging significantly influence pavement degradation, underscoring the need for targeted, sustainable maintenance and rehabilitation measures.